Dynamic changes in DNA methylation during postnatal development in zebra finches Taeniopygia guttata exposed to different temperatures. (9th May 2020) - Sheldon, Elizabeth L.; Schrey, Aaron. W.; Hurley, Laura L.; Griffith, Simon C.
Abstract : Epigenetic changes associated with early life conditions are known to play a significant role in shaping the adult phenotype. Studies of DNA methylation in wild animals are lacking, yet are important for understanding the fitness consequences of environmentally induced epigenetic change. In our study, we quantified variation in DNA methylation in wild, post‐hatch zebra finches Taeniopygia guttata developing at seasonally variable temperatures in the Australian desert. We also compared variation in DNA methylation among captive zebra finch siblings raised in temperature controlled 'hot' or 'cool' rooms. We detected an increase in genome‐wide levels of DNA methylation between day 3 and day 11 of post hatch development in wild zebra finches. In the wild, ambient temperatures were also found to affect genome‐wide levels of DNA methylation and plasticity in the methylation state of individual loci. Family effects had a significant influence on DNA methylation throughout our study, and while we did not detect an effect of temperature on DNA methylation levels in non‐related captive birds, our sibling pair analyses revealed that within families, elevated temperatures were associated with higher levels of DNA methylation. Our findings suggest a wide window in early development during which climatically induced variation in DNA methylation could occur. Further work is necessary to understand the potential for such variation to promote ecologically relevant variation in wild birds.